Septic thrombophlebitis of the superior mesenteric vein and multiple liver abscesses in a patient with Crohn's disease at onset - Grueso Jose; Beltrán Belen; Nos Pilar; Bastida Guillermo; Aguas Mariam; Grueso Julio (BMC Gastroenterology, 2007)
Abstract Background Portal-mesenteric vein thrombosis, pylephlebitis and liver abscesses are rare complications of inflammatory bowel disease (IBD). The purpose of this case report is to relate an unusual presentation of CD in order to show how conservative treatment could be an appropriate option as a bridge to the surgery, in patients with septic thrombophlebitis and multiple liver abscesses with CD. Case presentation We report a case of a 25-year-old man with Crohn's disease (CD) who developed a superior mesenteric venous thrombosis, multiple liver abscesses and pylephlebitis, diagnosed through abdominal ultrasound and an abdominal computed tomography (CT) scan. The patient was successfully treated with conservative treatment consisting of intravenous antibiotics, subcutaneous anticoagulation and percutaneous catheter drainage of liver abscesses. Conclusion We reported an unnusual case of pylephlebitis in CD. Until now this association has not been reported in adult patients at onset. We hypothesise that the infection developed as a result of mucosal disease and predisposed by corticoid therapy. Adequated management was discussed.